The effects of Sutherlandia frutescens extracts in cultured renal proximal and distal tubule epithelial cells - Alisa Phulukdaree; Devapregasan Moodley; Anil Chuturgoon (South African Journal of Science, 2010)
Sutherlandia frutescens (SF), a medicinal plant indigenous to South Africa, is traditionally used to treat a diverse range of illnesses, including cancer and viral infections. The biologically active compounds of SF are polar, thus renal elimination increases susceptibility to toxicity in that organ. This study investigated the antioxidant potential, lipid peroxidation, mitochondrial membrane potential and apoptotic induction by SF extracts on proximal and distal tubule epithelial cells. Cell viability was determined using the MTT assay. Mitochondrial membrane potential was determined using a flow cytometric JC-1 Mitoscreen assay. Cellular glutathione and apoptosis were measured using the GSH-Gloâ„¢ Glutathione assay and Caspase-GloÂ® 3/7 assay, respectively. The IC50 values from the cell viability results for LLC-PK1 and MDBK were 15 mg/mL and 7 mg/mL, respectively. SF extracts significantly decreased intracellular glutathione in LLC-PK1 (p < 0.0001) and MDBK (p < 0.0001) cells, while lipid peroxidation increased in treated LLC-PK1 (p < 0.0001) and MDBK (p < 0.0001) cells. JC-1 analysis showed that SF extracts promoted mitochondrial membrane depolarization in both LLC-PK1 and MDBK cells by up to 80% (p < 0.0001). The activity of caspase 3/7 increased in both LLC-PK1 (11.9-fold; p < 0.0001) and MDBK (2.2-fold; p < 0.0001) cells. SF extracts at high concentrations appear to increase oxidative stress, to alter mitochondrial membrane integrity, and to promote apoptosis in renal tubule epithelia.